Promover a saúde, produzir famílias: a implementação da Estratégia Saúde da Família na Encosta da Serra Gaúcha - Oliveira, Everton de (Universidade Federal de São Carlos, 2013)
The Family Health Strategy (FHS) is a health care policy that organizes much of the Primary Care of the Brazilian Health System, called SUS. By standing at a care level that aims a daily relationship with the population, the FHS is critically seen as a policy that segregates distinct social strata, as an instrument of state aimed at containment of a population regarded as poor . In this dissertation, I seek to problematize this issue starting from an ethnography conducted in the city here called São Martinho, situated in the region of Encosta da Serra, northeastern Rio Grande do Sul. Starting from this issue, my research question is: how is FHS constituted? To answer it, my goal is to analyze the process of implementation of the FHS in São Martinho, from a field research conducted between 2011 and 2013. The object of the analysis, thus, is dynamic, meaning that its composition is in motion, as an entanglement of subjects and spaces involved in this process, mapped into three smaller bundles of relationships: 1) concerning the medical care, 2) the assisted residents, and 3) the government and politics. In this dissertation, the description of what constitutes the FHS in this process will not refer to the figure of a state, nor to a system separated from the dynamics of the municipality in question: it will depend on the involvement and relationship of disparate subjects, in a entanglement that do not produces antagonisms, but everyday disputes that redraws its contours. The two basic signs of FHS, health and family, will also be the main object in dispute.
Keywords: Sociologia; Programa Saúde da Família (Brasil); Sistema Único de Saúde (Brasil); Família; Governo; CIENCIAS HUMANAS::SOCIOLOGIA